Analisis Pengaruh Pengadaan Karyawan dan Pengembangan Karir Terhadap Produktivitas Karyawan PT. Indonesia Epson - Crismayanti; Rakhmat; Budi Rachmawati (Mulia Pratama, 2024)
Employees are a determining factor in the success of achieving organizational goals and survival. If employee productivity is high, the organization will develop and organizational goals will be easily achieved. Career development is formed by indicators of promotion, rotation, demotion, psychological test, interview, education, job knowledge, job skills, required education and alternative education. If this is fulfilled, then PT Indonesia Epson Industry Indonesia. In order to increase work productivity, companies must be truly selective in selecting and appointing new employees. One of the factors to increase work productivity is the quality and physical abilities of employees. The quality and physical abilities of employees to increase employee work productivity are influenced by the level of education, training, work motivation, work ethic, mental and physical abilities of the employees concerned which will provide opportunities for employees to occupy higher positions. The importance of the PT Indonesia Epson Industry Indonesia career development program. Together there is an influence between the independent variables in the form of Employee Procurement and Career Development, on PT Indonesia Epson Industry Indonesia Employee Productivity. The hypothesis that Employee Procurement and Career Development jointly influence PT Indonesia Epson Industry Indonesia Employee Productivity has been proven to be true. This can be proven by the results of the F test data analysis, the calculated F value = 36.583 > F table = 3.22, and the significance level is 0.000 < 0.05, so Ho is rejected which means there is a joint influence between the independent variables in the form of Procurement Employees and Career Development on Employee Productivity of PT Indonesia Epson Industry Indonesia.